2009
DOI: 10.3349/ymj.2009.50.4.512
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Hepatitis A Virus in the South-East Area of Gyeonggi-do in Korea

Abstract: PurposeHepatitis A virus (HAV) has been a leading cause of acute hepatitis in Korea. The reported genotypes of acute hepatitis A in Korea are the subgenotype IA and IB. The aim of the present study is to investigate HAV genotypes in the south-east area of Gyeonggi-do in Korea.Materials and MethodsFrom June 2004 to June 2006, 46 acute hepatitis A patients were enrolled prospectively. All had sporadic acute hepatitis A patients. All suspected cases of acute hepatitis A were tested for IgM anti-HAV antibodies. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Until 2004, subgenotype IA was the most prevalent in the Republic of Korea [25]. However, studies conducted between 2004 and 2008 reported the cocirculation of the 2 prevalent subgenotypes IA and IIIA [22, 25, 26]. Subgenotype IIIA has been the predominant subgenotype since 2008, according to a previous study [22, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Until 2004, subgenotype IA was the most prevalent in the Republic of Korea [25]. However, studies conducted between 2004 and 2008 reported the cocirculation of the 2 prevalent subgenotypes IA and IIIA [22, 25, 26]. Subgenotype IIIA has been the predominant subgenotype since 2008, according to a previous study [22, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Until early 2000, almost all isolates tested had been identified as genotype IA [Byun et al, 2001]. However, studies conducted from 2004 to 2008 reported the co-circulation of the two prevalent genotypes IA and IIIA [Yoo et al, 2008;Yun et al, 2008;Park et al, 2009;Song et al, 2009]. More recent reports showed that genotype IIIA was the predominant serotype since 2008 Yoon et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, cross-reactivity could be only definitively excluded with the entire genome sequencing for the tested samples. However, co-circulation of the subgenotypes IA and IIIA has been reported in India [ 33 ] and of IA, IB and IIIA in Korea [ 34 ]. Co-circulation of the subgenotypes IA and IB in South Africa, South America, Europe and the US and the existence of recombination events between subgenotypes have also been observed [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%